Compassionate leaders influence nurses’ emotional healing during the COVID-19 crisis in hospitals - Elfiana, Elfiana; Yetti , Krisna; Kuntarti , Kuntarti; Widuri , Endang; Wulandari , Dyah Fitri; Rosnani, Rosnani (The Journal of Palembang Nursing Studies, 2024)
Background: The crisis situation during the pandemic has placed an additional burden on nurses regarding the care of COVID-19 patients. This is due to several factors, including the emergence of new disease variants, a rising number of cases, limited access to information, and nurses’ psychological well-being. Therefore, it is crucial for nurses to receive support from their leadership to effectively fulfill their roles Objective: To determine the key dimensions of compassionate leadership that have the greatest impact on the emotional well-being of nurses working in COVID-19 treatment rooms.  Methods: The research design employs a cross-sectional approach, with the independent variable being compassionate leadership, encompassing dimensions such as presence, understanding, empathy, and assistance. The dependent variable under examination is emotional healing. The sampling technique applied is purposive sampling, resulting in a sample size of 200 respondents across eight treatment rooms. Results: Nurses, on the whole, perceived their leaders’ implementation of compassionate leadership during the pandemic crisis as fairly adequate, scoring it at 66.4%. As for emotional healing among nurses, it was, on average, fulfilled to a level of 68.3%. Importantly, there exists a significant relationship between compassionate leadership and emotional healing. Specifically, among the dimensions of compassionate leadership, the one that had the most substantial influence on nurses’ emotional healing was “helping”. Conclusion: Amidst the COVID-19 pandemic crisis in hospitals, nurses required assistance and support from leadership to navigate the challenges encountered while actively providing care. These interventions could be effectively incorporated by nurses to complement ongoing tuberculosis treatment therapies.